2014
DOI: 10.1038/ng.2949
|View full text |Cite
|
Sign up to set email alerts
|

Triplication of a 21q22 region contributes to B cell transformation through HMGN1 overexpression and loss of histone H3 Lys27 trimethylation

Abstract: Down syndrome confers a 20-fold increased risk of B cell acute lymphoblastic leukemia (B-ALL)1 and polysomy 21 is the most frequent somatic aneuploidy amongst all B-ALLs2. Yet, the mechanistic links between chr.21 triplication and B-ALL remain undefined. Here we show that germline triplication of only 31 genes orthologous to human chr.21q22 confers murine progenitor B cell self-renewal in vitro, maturation defects in vivo, and B-ALL with either BCR-ABL or CRLF2 with activated JAK2. Chr.21q22 triplication suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 58 publications
4
133
0
5
Order By: Relevance
“…To test this hypothesis, the fi rst group was composed of Pax5 +/− mice and control littermate wild-type (WT) mice born and kept in a specifi c pathogen-free (SPF) environment during their lifespan. These Pax5 +/− mice did not spontaneously develop pB-ALL after 2 years, corroborating previous results ( 16,17 ). The second group was composed of Pax5 +/− mice and control littermate WT mice born and kept in the SPF environment until moved to a common infectious environment ( Fig.…”
Section: Introductionsupporting
confidence: 75%
“…To test this hypothesis, the fi rst group was composed of Pax5 +/− mice and control littermate wild-type (WT) mice born and kept in a specifi c pathogen-free (SPF) environment during their lifespan. These Pax5 +/− mice did not spontaneously develop pB-ALL after 2 years, corroborating previous results ( 16,17 ). The second group was composed of Pax5 +/− mice and control littermate WT mice born and kept in the SPF environment until moved to a common infectious environment ( Fig.…”
Section: Introductionsupporting
confidence: 75%
“…Defects specific to certain aneuploidies as well as defects observed in all aneuploid strains analyzed were evident in our aneuploid HSCs. The lineage-specific defects such as reduced B-cell number observed in trisomy 16 FL-HSC reconstitutions are likely due to chromosome-specific effects, as B-cell differentiation defects have also been observed in DS (Roy et al 2012;Lane et al 2014). Furthermore, we observed decreased proliferative potential in all aneuploidy models that we examined.…”
Section: The Effects Of Aneuploidy and Cin On Hsc Fitness And Hematopmentioning
confidence: 50%
“…13 It was recently shown that trisomy 21 leads to overexpression of HMGN1, which may promote B-lineage ALL by suppressing trimethylation of lysine 27 of histone H3. 14 The risk of all major groups of malignant solid tumors was decreased with the exception of testicular cancer. The risk of solid tumors was significantly reduced for men and women over 40 years of age; among the oldest age groups the cancer incidence was only 25% of that seen in the general population.…”
Section: Discussionmentioning
confidence: 99%